THE MAIN DIRECTIONS OF PUBLIC FINANCE MANAGEMENT REFORM IN THE REPUBLIC OF UZBEKISTAN - Bobomurotova Manzura Panjievna (Scholars Digest Publishing, 2023)
The article is devoted to the reform of public financial management in the Republic of Uzbekistan, the information base of which was composed of laws, regulations and information materials about the country's public finance system and its development in accordance with the directions and activities defined by two strategies for the reform of public financial management of the Republic of Uzbekistan. The article shows the relevance, purpose and objectives of the reform, describes the stages of development of the public finance system of Uzbekistan, the achieved results, problems and directions for its further improvement.
Keywords: public finance, public financial management reform, fiscal transparency, financial control, proactive budgeting, medium-term planning, strategic planning.